THE LACK OF LANGUAGE ATTITUDE AMONG BATAKNESE TEENAGERS TOWARDS SECOND LANGUAGE ACQUISITION - MARLINA TAMPUBOLON (JURNAL ILMIAH MAKSITEK, 2019)
This research deals with language attitude and language acqusition. One language is different to other languages in this world. It insists the language user have to create the important way to maintain. Language attitude has the important role in maintaining one language. The language acquisition will be also influenced by the language attitude whether it is positive or negative. If one vernacular can be maintained by its user, it will be survived in the society or vice versa it will be lost and its acquisition is affected negatively. In other words, it can be defined that there will be a language sound change of one vernacular and it can make one language has lost its identity if the users has the negative language attitude. Batak language is one of the vernaculars in Indonesian and most dominantly used in North Sumatra. In this mini research, it will be presented that the existence of Batak language is going to be shifted by other language.